EFFECTS OF RELIGIOUS VERSUS STANDARD COGNITIVE‐BEHAVIORAL THERAPY ON OPTIMISM IN PERSONS WITH MAJOR DEPRESSION AND CHRONIC MEDICAL ILLNESS. Issue 11 (28th July 2015) - Koenig, Harold G.; Pearce, Michelle J.; Nelson, Bruce; Daher, Noha
Abstract : Background: We compared the effectiveness of religiously integrated cognitive behavioral therapy (RCBT) versus standard CBT (SCBT) on increasing optimism in persons with major depressive disorder (MDD) and chronic medical illness. Methods: Participants aged 18–85 were randomized to either RCBT ( n = 65) or SCBT ( n = 67) to receive ten 50‐min sessions remotely (94% by telephone) over 12 weeks. Optimism was assessed at baseline, 12 and 24 weeks by the Life Orientation Test‐Revised. Religiosity was assessed at baseline using a 29‐item scale composed of religious importance, individual religious practices, intrinsic religiosity, and daily spiritual experiences. Mixed effects growth curve models were used to compare the effects of treatment group on trajectory of change in optimism. Results: In the intention‐to‐treat analysis, both RCBT and SCBT increased optimism over time, although there was no significant difference between treatment groups ( B = –0.75, SE = 0.57, t = –1.33, P = .185). Analyses in the highly religious and in the per protocol analysis indicated similar results. Higher baseline religiosity predicted an increase in optimism over time ( B = 0.07, SE = 0.02, t = 4.12, P < .0001), and higher baseline optimism predicted a faster decline in depressive symptoms over time ( B = −0.61, SE = 0.10, t = −6.30, P < .0001), both independent of treatment group. Conclusions: RCBT and SCBT are equally effective in increasing optimism in persons with MDD and chronic medical illness. While baseline religiosity does not moderate this effect, religiosity predicts increases in optimism over time independent of treatment group.